Peran Kepemimpinan dan Motivasi terhadap Kinerja Karyawan - Diah Angguningtiyas; Lingga Yuliana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purpose of this study was to determine the implementation of leadership and motivation on employee performance by taking a case study at PT Puncak Jaya Samudra. This study uses a descriptive qualitative method. Data were obtained by observation, interview and documentation methods. The results of this study indicate that in motivating and improving employee performance, namely by implementing a democratic leadership system, leaders provide motivation in various forms including: providing salaries, providing holiday allowances, providing year-end bonuses, providing health facilities, holding training, seminars and career paths. The impact of work motivation provided by the leadership of PT Puncak Jaya Samudra (PJS) is increasing employee performance, employees can be responsible and have high work enthusiasm.